Strategic Management Practices and Organizational Performance of Business Process Outsourcing Companies in Nairobi County, Kenya - Doris Ndiritu; Anyieni Abel (Equivalent : Journal of Economic, Accounting and Management, 2025)
Purpose the study sought to assess the effect of strategic management practices on performance of Business Process Outsourcing entities based in Nairobi County, Kenya. This was motivated by decreasing performance and growth of BPOs, despite the growing demand of outsourced services by local and international corporates. Methodology this study utilized descriptive research design and it targeted 1257 employees drawn from the 118 business process outsourcing companies in Nairobi County. Using sampling formula, the study sampled 113 respondents. A questionnaire was utilized to obtain data, which was analysed using descriptive and inferential statistics. Results, The findings revealed that strategic leadership, strategic planning, resource mobilization, and strategic culture alignment although not effectively upheld by most of the surveyed BPOs were significant in stimulating the performance of the BPOs. Practical Implications for Economic Growth and Development, While it is evident that business process outsourcing is essential in steering growth and efficiency in other sectors, the BPOs have not been performing well, exposing the overall economy as their downfall would see loss of jobs and decline on government revenue. It is therefore essential for the managers of the BPOs to proactively integrate strategic management practices to adequately and rapidly respond to changes external environment thus steering their continued performance.